Kim - Kipling, Rudyard (New York The Modern Library, 1928)
An exciting and touching tale of an Irish orphan-boy who has lived free in the streets of Lahore before setting out, with a Tibetan Lama, on a double quest. This eventually leads to enrollment in the Indian Secret Service and a thrilling climax in the Himalayas.
Keywords: India -- Orphans